PENGARUH PROFITABILITY, FIRM SIZE DAN PRICE EARNING RATIO TERHADAP CAPITAL STRUCTURE PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2010-2015 - B31112079, UMI ZULFIA TURROHMAH (Jurnal Manajemen Update, 2016)
The type of research used in this research is quantitative research. Food and Beverage Company in the Consumer Goods Industry Sector Manufacturing company listed on the Stock Exchange in 2010-2015 there is a population of 18 companies, in the amount there were 14 companies meeting the criteria established research sample. Analyzed using descriptive statistics, regression analysis and classical assumption with 20:00 SPSS for windows. This study examined about the factors that affect the company's capital structure Food and Beverage Industry Sector Consumer Goods Manufacturing in companies listed on the Stock Exchange in 2010-2015 . Eighteen companies Food and Beverage Sector Consumer Goods Industry on Manufacturing company, fourteen companies that meet the criteria to be tested . This study found three independent variables in the test is Return on Assets ( ROA ) , Firm Size ( company size ) and Price Earning Ratio ( PER ) , while the dependent variable is the Debt to Assets Ratio ( DAR ) . The results partially (t test) showed that Profitability (Return On Assets), Firm Size (company size) and Price Earning Ratio (PER) positive and significant impact on the Capital Structure (Debt to Assets Ratio), while the simultaneous testing (Testing F) showed that Profitability (Return on Assets), Firm Size (company size) and Price Earning Ratio (PER) positive and significant impact on the Capital Structure (Debt to Assets Ratio). Keywords : Profitability (Return On Assets), Firm Size (company size) and Price Earning Ratio (PER), Capital Structure (Debt To Assets Ratio).